MORPHOLOGICAL VARIATIONS AND CLINICAL IMPLICATIONS OF THE INFERIOR ALVEOLAR ARTERY - Victoria Roxana Ivaşcu (Romanian Journal of Oral Rehabilitation, 2020)
The inferior alveolar artery (IAA), a collateral branch of the maxillary artery, is mainly responsible for the vascularization of the mandibular tooth-gum-alveolar bone units. In its course from the infratemporal region to the body of the mandible, the IAA may exhibit variations in both origin and trajectory. This study analyses the anatomical variations of the IAA and describes potential clinical complications following different surgical procedures in the mandible. A comprehensive literature review across Clarivate Analytics/Thomson Web of Knowledge and PubMed databases was conducted. The following keywords were used: inferior alveolar artery, anatomical variations, posterior mandible, clinical consequences. Data from similar previous personal research were also added to the findings. The results of this study suggest that the posterior mandible remains the major risk area for damage to the IAA.